Adaptability of Siheyuan (四合院) spatial arrangement in Chinese houses in Kampung Ketandan, Yogyakarta, Indonesia - Ristya Arinta Safitri; T. Yoyok Wahyu Subroto; Dwita Hadi Rahmi (Built Heritage)
Abstract Economic, social and political factors are the main triggers of human migration, which aims to enable people to obtain better livelihoods. Chinese people are among the ethnic groups that have migrated and settled in Southeast Asian countries, including Indonesia. The traditional Chinese dwelling known as a courtyard house or Siheyuan (四 合 院) is one of the cultural forms brought by Chinese migrants to this recipient region. This type of dwelling might require adjustments due to climatic conditions, materials, and the desire to be accepted by the local community. Therefore, what adaptations have been made by members of the Chinese diaspora living in Yogyakarta city? This research aims to explore the adaptation of the spatial arrangement of Chinese houses in Kampung Ketandan, which is a Chinese settlement that has existed for 200 years in Yogyakarta city and is associated with Javanese culture. This research uses a qualitative method to collect data concerning 6 original Chinese houses through observation and interviews. The analytical process involves spatial zone analysis and an access graph. As a result, the transformation and modification that characterise courtyards and spatial arrangements in Ketandan, Yogyakarta, are revealed.